2016
DOI: 10.1002/alr.21773
|View full text |Cite
|
Sign up to set email alerts
|

Gender‐specific analysis of outcomes from endoscopic sinus surgery for chronic rhinosinusitis

Abstract: Both male and female CRS patients showed significant and durable symptom relief following ESS. Women reported higher symptom burden prior to surgery, and in the early postoperative period. However, after 1-year post-ESS, both genders showed similar symptom scores. The trend and magnitude of improvement were similar in both genders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
53
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(61 citation statements)
references
References 15 publications
5
53
1
Order By: Relevance
“…Stein et al . identified gender as a risk factor as well and there is an increasing body of research to suggest that there are gender‐dependent differences in patients with CRS . A family history of CRS was also identified as a risk for requiring revision surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Stein et al . identified gender as a risk factor as well and there is an increasing body of research to suggest that there are gender‐dependent differences in patients with CRS . A family history of CRS was also identified as a risk for requiring revision surgery.…”
Section: Discussionmentioning
confidence: 99%
“…While ESS may have been performed in these cohorts for recurrent acute sinusitis, mucoceles, etc., and polyp status may have been underreported (based on diagnosis and coding oversight), it is logical to assume that many of these procedures—primary or recurrent—were conducted on patients with CRSsNP. In our own series of CRS patients undergoing ESS in a tertiary care practice, CRSsNP patients comprise approximately one‐half the number of subjects …”
mentioning
confidence: 99%
“…Of note, 55.2% of all patients electing ESS were male with a significantly higher proportion of males in the 50 years and older group. Prior research by Lal et al . showed that men report significantly lower SNOT‐22 scores when compared to women with a decline in SNOT‐22 scores with age for both sexes.…”
Section: Discussionmentioning
confidence: 93%